Necessity of strengthening neurology services in Nepal - Piryani, R M; Poudel, R S (Journal of Chitwan Medical College, 2015)
Dear Editor, Stroke, head injuries and epilepsy are common neurological problems reported worldwide including Nepal. Nepal also bears the burden of nervous system infection such as meningitis, cerebral malaria, Japanese B encephalitis. The average life expectancy of Nepalese population has increased noticeably in the last twelve years; hence it may lead to increase in age related neurological conditions such as dementia, Parkinson disease. Because of poor road condition, rapidly increasing number of two- wheelers, disorganized traffic pattern, and lack of driving discipline in Nepal, motor vehicles accidents are on rise, so the head injuries too. The accompanied person along for the ride on two- wheel vehicles are not required to wear helmet and passengers in four wheelers avoid using safety belts are at risk. Moreover, the implementation of legislation to prevent driving in drunken state is limited. Presently some of the government hospitals, private medical college teaching hospitals and corporate sector hospitals located in urban areas provide neurological services. However, a large number of patients of sub-urban and rural areas having common neurological aliments have limited access. Ignorance, illiteracy, limited resources, negative attitude, discrimination, faith on traditional healers and weak economical status may be the limiting factor to access. Establishing neurological services network with public private partnership and use of latest technology may improve care and delivery of neurological services in country. At the same time government need to 1) motivate, encourage and facilitate young doctors to get training in neurosurgery and neuromedicine, 2) invest in infrastructure development, 3) create awareness among public especially of suburban and rural areas and 4) promote research. These approaches may improve quality of care and service delivery. Sincerely Dr. Rano Mal Piryani- Prof of Medicine and Medical Education, Chitwan Medical College Mr. Ramesh Sharma Poudel- Pharmacist, Pharmacy, Chitwan Medical College Teaching Hospital